2010
DOI: 10.1093/eurheartj/ehq325
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor vs. clopidogrel in patients with acute coronary syndromes and diabetes: a substudy from the PLATelet inhibition and patient Outcomes (PLATO) trial

Abstract: AimsPatients with diabetes mellitus (DM) have high platelet reactivity and are at increased risk of ischaemic events and bleeding post-acute coronary syndromes (ACS). In the PLATelet inhibition and patient Outcomes (PLATO) trial, ticagrelor reduced the primary composite endpoint of cardiovascular death, myocardial infarction, or stroke, but with similar rates of major bleeding compared with clopidogrel. We aimed to investigate the outcome with ticagrelor vs. clopidogrel in patients with DM or poor glycaemic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
238
2
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(269 citation statements)
references
References 20 publications
17
238
2
12
Order By: Relevance
“…In the setting of PCI, stent thrombosis is a catastrophic complication leading to death or myocardial infarction and several studies report a strong association with the presence of diabetes 19. Subgroup analyses in both The Trial to Assess Improvement in Therapeutic Outcomes by Optimizing Platelet Inhibition With Prasugrel‐Thrombolysis in Myocardial Infarction 38 (TRITON‐TIMI 38) 20 and the PLATelet inhibition and patient Outcomes (PLATO) trial 21 confirmed the beneficial role of more powerful antiplatelet agents when compared with clopidogrel in the diabetic arm but even so, this population had ischemic outcomes that were approximately 20% higher than in the non‐diabetic population. Dual antiplatelet therapy is not currently recommended in primary prevention in patients with diabetes and, in secondary prevention, it is only recommended for 12 months 22.…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of PCI, stent thrombosis is a catastrophic complication leading to death or myocardial infarction and several studies report a strong association with the presence of diabetes 19. Subgroup analyses in both The Trial to Assess Improvement in Therapeutic Outcomes by Optimizing Platelet Inhibition With Prasugrel‐Thrombolysis in Myocardial Infarction 38 (TRITON‐TIMI 38) 20 and the PLATelet inhibition and patient Outcomes (PLATO) trial 21 confirmed the beneficial role of more powerful antiplatelet agents when compared with clopidogrel in the diabetic arm but even so, this population had ischemic outcomes that were approximately 20% higher than in the non‐diabetic population. Dual antiplatelet therapy is not currently recommended in primary prevention in patients with diabetes and, in secondary prevention, it is only recommended for 12 months 22.…”
Section: Discussionmentioning
confidence: 99%
“…In routine clinical practice, physician decisions about antiplatelet therapy choice may be based on several factors unique to the individual patient, including predicted risk of recurrent events, predicted safety, and cost of treatment. Although patients with diabetes mellitus have been shown to benefit from higher‐potency P2Y 12 inhibitor therapy,26, 27 diabetes mellitus was not a significant factor associated with P2Y 12 inhibitor intensification. Bleeding before the recurrent ischemic event was rare, and its rarity likely explains its lack of statistically significant association with P2Y 12 inhibitor intensification.…”
Section: Discussionmentioning
confidence: 86%
“…23 In patients with DM, the reduction in major adverse cardiovascular events was similar to the overall population, with a 2.1% absolute risk reduction. 52 There was also a trend toward a reduction in stent thrombosis among diabetic patients.…”
Section: Antiplatelet Therapymentioning
confidence: 95%